2014
DOI: 10.4137/bci.s18863
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A Inhibits STAT3 and Induces Tumor Cell Death in Neuroblastoma and Multiple Myeloma

Abstract: Signal transducer and activator of transcription 3 (STAT3) is an oncogenic transcription factor that has been implicated in many human cancers and has emerged as an ideal target for cancer therapy. Withaferin A (WFA) is a natural product with promising antiproliferative properties through its association with a number of molecular targets including STAT3. However, the effect of WFA in pediatric neuroblastoma (NB) and its interaction with STAT3 have not been reported. In this study, we found that WFA effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
(85 reference statements)
2
28
0
Order By: Relevance
“…STAT3 inhibiting capacity of WFA has been reported recently (Table 1). By using neuroblastoma and multiple myeloma tumor cells, Yco et al demonstrated that WFA induced dosedependent cell death and blocked the transcriptional activity of STAT3 by inhibition of SAT3 phosphorylation (Tyr705) [11]. In silico molecular docking analysis revealed the possibility of intermolecular interaction between WFA with STAT3 in the SH2 domain.…”
Section: Transcription Factors a Nf-κbmentioning
confidence: 98%
See 3 more Smart Citations
“…STAT3 inhibiting capacity of WFA has been reported recently (Table 1). By using neuroblastoma and multiple myeloma tumor cells, Yco et al demonstrated that WFA induced dosedependent cell death and blocked the transcriptional activity of STAT3 by inhibition of SAT3 phosphorylation (Tyr705) [11]. In silico molecular docking analysis revealed the possibility of intermolecular interaction between WFA with STAT3 in the SH2 domain.…”
Section: Transcription Factors a Nf-κbmentioning
confidence: 98%
“…SH2 domain typically functions as a phosphorylated tyrosine recognition domain on other proteins hence playing crucial role in signal transduction. It is postulated that binding of WFA can directly block dimer formation via changes in physical-chemical factors, such as charge, hydrogen binding, solvent accessibility, and side-chain conformations [11]. WFA also inhibits growth of human breast cancer cells by inhibiting constitutive as well as IL-6-inducible phosphorylation of STAT3 (Tyr 705) [97].…”
Section: Transcription Factors a Nf-κbmentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 Studies have suggested that the persistent activation of Stat3 plays a key role in resistance to apoptosis of signal transduction pathways in hepatocellular carcinoma. 40 combination of PeI-MZF-NPs and hsV-TK/gcV for treatment of hepatoma…”
mentioning
confidence: 99%